2019
DOI: 10.1192/bjb.2019.78
|View full text |Cite
|
Sign up to set email alerts
|

The emotional and mental health needs of young carers: what psychiatry can do

Abstract: Aims and methodTo review the literature on the emotional and mental health needs of young carers of parents with mental illness and the extent to which such needs are recognised and supported by professionals. Three databases were systematically searched from 2008 to 2018, and five studies met the inclusion criteria.ResultsThe key findings were that young caregivers had a significantly higher dose-response mortality risk than their peers; were at increased risk of mental health difficulties, especially where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A substantial body of published international research provides evidence on the adverse psychosocial impacts on youth caring for a family member, particularly a parent, who has a serious mental or physical health condition [ 1 , 2 , 3 , 4 ]. Most studies in this field have investigated children and adolescents up to the age of 18 years (referred to as young carers), with markedly less research on young adult carers (18–24 years) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of published international research provides evidence on the adverse psychosocial impacts on youth caring for a family member, particularly a parent, who has a serious mental or physical health condition [ 1 , 2 , 3 , 4 ]. Most studies in this field have investigated children and adolescents up to the age of 18 years (referred to as young carers), with markedly less research on young adult carers (18–24 years) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that adolescents and young adults with caring roles spent about 3–5 h helping each day (Haugland et al 2019 ). Due to their responsibilities, these young carers’ day-to-day lives can be stressful (e.g., Ali et al 2012 ), with potential risks to their own mental health (e.g., Dharampal and Ani 2020 ). However, not all young carers experience adverse impacts on their emotional well-being (e.g., Svanberg et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A caring role influences youth's lives in various wayspositively and negatively (Joseph et al, 2009). Concerning mental health, scholars have highlighted risks for potential adverse outcomes due to caring (e.g., Dharampal & Ani, 2020). However, the small number of comparative studies, broad age ranges, and a lack of theoretical foundation limit the understanding of the observed association between youth's carer role status and mental health.…”
mentioning
confidence: 99%